EFFECT OF THE NEW BIOLOGICAL PRODUCT CREATED ON THE BASIS OF TRICHODERMA ON SOIL MICROORGANISMS AND PLANTS OF DIFFERENT TAXONS (Academicia Globe: Inderscience Research, 2023)
The environmental assessment of a new biocomposite preparation based on Trichoderma sp. L-6, L-3, and D-11 strains for the biodegradation of crop residues was carried out under the conditions of model experiments.